Transgenic Animal Models to Visualize Cancer-Related Cellular Processes by Bioluminescence Imaging - Manni, Isabella; de Latouliere, Luisa; Gurtner, Aymone; Piaggio, Giulia (Frontiers in Pharmacology, 2019)
Preclinical animal models are valuable tools to improve treatments of malignant diseases, being an intermediate step of experimentation between cell culture and human clinical trials. Among different animal models frequently used in cancer research are mouse and, more recently, zebrafish models. Indeed, most of the cellular pathways are highly conserved between human, mouse and zebrafish, thus rendering these models very attractive. Recently, several transgenic reporter mice and zebrafishes have been generated in which the luciferase reporter gene are placed under the control of a promoter whose activity is strictly related to specific cancer cellular processes. Other mouse models have been generated by the cDNA luciferase knockin in the locus of a gene whose expression/activity has increased in cancer. Using BioLuminescence Imaging (BLI), we have now the opportunity to spatiotemporal visualize cell behaviors, among which proliferation, apoptosis, migration and immune responses, in any body district in living animal in a time frame process. We provide here a review of the available models to visualized cancer and cancer-associated events in living animals by BLI and as they have been successful in identifying new stages of early tumor progression, new interactions between different tissues and new therapeutic responsiveness.